2016
DOI: 10.1007/s00228-016-2166-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with expression of extrapyramidal symptoms in users of atypical antipsychotics

Abstract: The occurrence of EPS in SGA users is a common finding, with no difference of antipsychotics studied in relation to the risk of extrapyramidal manifestations. The adjunctive use of carbamazepine may predispose the user of SGA to the occurrence of EPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Carbamazepine‐induced dyskinesias were reported due to intoxication67 or concomitant use of lithium 68. Interestingly, one study found that co‐administration of carbamazepine and a second‐generation antipsychotic increased the risk of movement disorders 69. In a study, 201 patients with epilepsy were evaluated by a movement disorders specialist for the presence of movement disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Carbamazepine‐induced dyskinesias were reported due to intoxication67 or concomitant use of lithium 68. Interestingly, one study found that co‐administration of carbamazepine and a second‐generation antipsychotic increased the risk of movement disorders 69. In a study, 201 patients with epilepsy were evaluated by a movement disorders specialist for the presence of movement disorders.…”
Section: Resultsmentioning
confidence: 99%